Suíte Macambira de Clóvis Pereira: o violoncelo entre o erudito e a tradição - Lauriza Valkíria Anastácio (2024)
This paper investigates the aspects of Northeastern popular tradition music and the Armorial Movement present in the wok “Suíte Macambira” for solo cello, by composer Clóvis Pereira. Theses aspects are related to the idiomatic elements of the cello in classical music.The paper provides a summary of elements from these musical tradition and describes the role they played in the composer’s career. It also addresses how Clóvis uses tools from Notheastern popular tradition and Armorial music in the writing for cello in three movements of the “Suíte Macambira”. Finally, aiming to highlight the elements of Northeastern tradition in the interpretation of the piece, it suggests interpretative approaches for these three movements: the Preludio, the Canto do Cego, and the Coco Agalopado.